Now you see, now you don’t - a radiopaque neck mass? - Shalihin, Mohd Shaiful Ehsan; Amir Hamzah, Azwan Faiz; Abidin, Mohd Radhwan (Malaysian Medical Association, 2020)
Chest X-ray is valuable in the primary care setting in helping clinicians to confirm the underlying findings of the respiratory and cardiovascular systems. This view also includes the lower cervical vertebrae region which is helpful in elaborating the findings surrounding the neck. However, a single view of the film may sometimes cause confusion regarding the exact origin of the abnormal signs of the X-ray images. Thus, clinical correlation and application of ‘rule of two’ in X-ray imaging is definitely useful to clarify the findings and avoiding any misdiagnosis, medical errors and non-justifiable further investigations. Here we report a case of an 18-year-old female student with abnormal radiopaque neck mass seen from her chest the X-ray image. She was clinically well without any significant clinical findings. Surprisingly, the findings totally resolved after repeat the X- ray at two different occasions within the same week. This strange abnormal finding was later confirmed to be her hair tier. She was saved from unnecessary investigations for tuberculosis and thyroid disorder by repeating the X-ray (rule of two occasions). Now you see, now you don’t of X-ray findings is indeed illogical and technical error needs to be rule out.